When maternal periconceptional diet affects neurological development, it’s time to think - Sinclair, Kevin D. (National Academy of Sciences, 2018)
There is increasing awareness that the nutritional status of women at the onset of pregnancy can have a profound effect on the general health and well-being of children. However, recent analyses indicate that the majority of women from different socioeconomic backgrounds are ill prepared for the nutritional rigors of pregnancy, and that outcomes of dietary interventions once pregnancy has commenced are usually disappointing (1). It follows that current thinking is moving toward more targeted dietary advice for intending parents with the aim of improving nutritional status by the time of conception. There is certainly compelling evidence from animal studies to identify this as perhaps the most critical stage of mammalian development: one that is acutely sensitive to subtle alterations in maternal diet with far-reaching consequences for the development of late-onset noncommunicable diseases (2, 3). However, to date, animal studies have focused, for the most part, on aspects of cardiometabolic health. In PNAS, Gould et al. (4) report that modest protein restriction (a low-protein diet) in mice limited to the period of preimplantation embryo development (termed Emb-LPD) initially leads to a reduction in the population of neural stem cells but then, upon dietary realignment, subsequently results in an enhancement of neuronal differentiation within higher regions of the fetal brain. Furthermore, they report that this apparently early adaptive response ultimately leads to deficits of short-term memory in young-adult offspring. These observations therefore greatly extend those of previous studies on brain function, which have generally explored the effects of dietary restriction throughout gestation and lactation (5), to highlight the importance of nutrition during the periconceptional period.